The Effect of Progressive Muscle Relaxation on the Value of Ankle Brachial Index and Foot Sensitivity in Patients with Diabetes Mellitus - Widiastuti, Agung; Ulkhasanah, Muzaroah Ermawati (GLOBAL HEALTH SCIENCE GROUP, 2024)
Diabetes mellitus (DM) is a global health threat due to many other health risks such as kidney failure, heart disease, stroke and even serious injuries that can cause complications. One of the complications is peripheral neuropathy nerve damage that causes diabetic ulcers so that there is a risk of decreased foot sensitivity and changes in ankle brachial index values in diabetics. Progressive muscle relaxation technique is one of the actions that can affect the hypothalamus to regulate and reduce the activity of the sympathetic nervous system to provide direction by moving the feet slowly and regularly. Objective: to determine the effect of progressive relaxation techniques on the value of ankle brachial index and foot sensitivity in patients with diabetes mellitus. Methods: This study used quasi experiment method with pre test and post test design approach with control group. The population of DM patients was 120 respondents, then the sample was taken using non-probability sampling and based on inclusion and exclusion criteria. Sampling using total sampling with the number of respondents 15 intervention groups and 15 control groups. Analysis using the t-test. Results: The results of the study on the ABI value obtained a p-value of 0.02 in the intervention group and a p-value of 0.414 in the control group while the foot sensitivity value obtained a p-value of 0.01 in the intervention group and 0.07 in the control group. Conclusion: This shows that there is an increase in ABI values and foot sensitivity in patients with diabetes mellitus. The progressive relaxation technique can be used as an intervention to prevent diabetic foot ulcers.